2019
DOI: 10.21873/anticanres.13949
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tumor Grade and Nodal Status in Oropharyngeal and Oral Cavity Squamous-cell Carcinoma Using a Radiomic Approach

Abstract: Background/Aim: To investigate whether a radiomic machine learning (ML) approach employing texture-analysis (TA) features extracted from primary tumor lesions (PTLs) is able to predict tumor grade (TG) and nodal status (NS) in patients with oropharyngeal (OP) and oral cavity (OC) squamous-cell carcinoma (SCC). Patients and Methods: Contrast-enhanced CT images of 40 patients with OP and OC SCC were post-processed to extract TA features from PTLs. A feature selection method and different ML algorithms were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 40 publications
0
54
0
1
Order By: Relevance
“…It has been proved the correlation between radiomics features and tumor phenotype (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Many studies have found Adc can be predicted by radiomics (22)(23)(24)(25)(26)(27)(28). Tang et al (27) developed a radiomics model to discriminate Adc from squamous cell carcinoma (Sqc) with an AUC of 0.82, Yang et al (24) developed an LR model to predict lymph node metastasis in solid Adc with an AUC of 0.86.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved the correlation between radiomics features and tumor phenotype (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Many studies have found Adc can be predicted by radiomics (22)(23)(24)(25)(26)(27)(28). Tang et al (27) developed a radiomics model to discriminate Adc from squamous cell carcinoma (Sqc) with an AUC of 0.82, Yang et al (24) developed an LR model to predict lymph node metastasis in solid Adc with an AUC of 0.86.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that radiomics features have great potential to be the maker for tumor phenotype (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and found Adc can be differentiated from Sqc by radiomics (17)(18)(19)(20)(21)(22)(23). However, The data sets of those studies only included Adc and Sqc, that is to say, the accuracy of those models will be affected by other histological subtypes of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Knime Analytics Platform (version 3.7.1) was used for variable selection and the implementation of the algorithms. The Knime Analytics Platform version 3.7.1 was chosen since it is a well-known analytics platform already used in previous studies 58,59 and it resulted as the best choice for advanced users in a comparison with other platforms and programming languages 60 . It allows the users to create workflows of ML analyses by combining nodes and is integrated with other software, thus allowing other researchers a high reproducibility of the analysis.…”
Section: Methodsmentioning
confidence: 99%